Asbestos-related Diseases - Otsuki, Takemi (IntechOpen, 2020)
The issue of asbestos exposure and the resulting health problems is now a global problem. The World Health Organization (WHO) has made recommendations on the eradication of asbestos-related diseases. However, malignant mesothelioma, mainly due to asbestos exposure, is a refractory malignant tumor, and technological innovation in diagnosis and treatment is required. In this context, this book describes the immunological effects of asbestos exposure, blood biomarkers, the pathology of malignant mesothelioma, and the status of immune checkpoint drugs in the treatment of malignant mesothelioma, along with the status of MMP mesothelioma. Concerns about health hazards associated with asbestos exposure may persist for many years to come. We hope this book will help researchers in this area.